0718 The Role of Polysomnography in Tracheostomy Decannulation of Children with Craniofacial Abnormalities. (12th April 2019) - Quinlan, Courtney; Piccione, Joseph; Afolabi-Brown, Olufunke
Abstract: Introduction: Patients with craniofacial abnormalities are at high risk for upper airway obstruction requiring tracheostomy. While guidelines for care of children requiring tracheostomy exist, decannulation practices vary amongst centers. The use of polysomnography (PSG) is one important variable in which best practices are not established. We hypothesized that tracheostomy dependent children with craniofacial abnormalities who had a pre-decannulation PSG in our institution have a higher decannulation success rate than those without a pre-decannulation PSG. Methods: This is a retrospective cohort study comparing decannulation outcomes between children with craniofacial abnormalities who underwent pre-decannulation PSG and those who did not between Jan 1, 2007 and June 1, 2017. Data on patient demographics, PSG results and medical comorbidities was abstracted from medical records. Results: Forty-five patients with craniofacial abnormalities were considered for tracheostomy decannulation. Twenty-five patients (55%) had a pre-decannulation PSG while twenty (45%) did not. Of those who had PSG, 4 (16%) did not undergo decannulation attempt due to the presence of obstructive sleep apnea (OSA); 9 (36%) had OSA and were decannulated successfully after medical or surgical intervention; 4 (16%) had evidence of OSA, but were successfully decannulated without intervention; and 8 (32%) had normal PSG findings. One (4%) patient with normal pre-decannulation PSG failed decannulation. One (5%) patient without pre-decannulation PSG failed decannulation. There were no statistically significant differences observed in decannulation success rates between patients with pre-decannulation PSG and those without. Conclusion: While no significant differences were observed in the decannulation success rate of patients who had pre-decannulation PSG compared to those who did not, significant OSA was noted in a large proportion of patients, influencing their decannulation process. While decision to obtain a pre-decannulation PSG is made on an individual basis, it is likely that a significant proportion of those children have undiagnosed OSA. These results suggest that while successful decannulation can be achieved in those with OSA, there is an important role for pre-decannulation PSG in children with craniofacial abnormalities due to the high prevalence of OSA in this population. Support (If Any): n/a